Correlation Between APOBEC3B Expression and Clinical Characterization in Lower-Grade Gliomas - Zhang, Hao; Chen, Zhiyang; Wang, Zeyu; Dai, Ziyu; Hu, Zhengang; Zhang, Xun; Hu, Min; Liu, Zhixiong; Cheng, Quan (Frontiers in Oncology, 2021)
Background As the most aggressive tumors in the central nervous system, gliomas have poor prognosis and limited therapy methods. Immunotherapy has become promising in the treatment of gliomas. Here, we explored the expression pattern of APOBEC3B, a genomic mutation inducer, in gliomas to assess its value as an immune biomarker and immunotherapeutic target. Methods We mined transcriptional data from two publicly available genomic datasets, TCGA and CGGA, to investigate the relevance between APOBEC3B and clinical characterizations including tumor classifications, patient prognosis, and immune infiltrating features in gliomas. We especially explored the correlation between APOBEC3B and tumor mutations. Samples from Xiangya cohort were used for immunohistochemistry staining. Results Our findings demonstrated that APOBEC3B expression level was relatively high in advanced gliomas and other cancer types, which indicated poorer prognosis. APOBEC3B also stratified patients’ survival in Xiangya cohort. APOBEC3B was significantly associated with infiltrating immune and stromal cell types in the tumor microenvironment. Notably, APOBEC3B was involved in tumor mutation and strongly correlated with the regulation of oncogenic genes. Conclusion Our findings identified that APOBEC3B could be a latent molecular target in gliomas.